Guest

Substituting x = – 3 in x^2 + 5x gives (– 3)^2 +5(–3) = – 9–15 = – 24

Substituting x = – 3 in
x^2 + 5x gives (– 3)^2 +5(–3) = – 9–15 = – 24

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5963 Points
one year ago
Dear Student

Substituting x =–3 in x^2+5x
x^2+5x = (–3)^2+5(–3) = 9–15 = -6.
This is the incorrect answer

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free